On one unsightly page in Soviet science hystory. A regular session of All-Union Lenin Academy of Agriculture Sciences of 1948 - Volotovski, Igor D. (Journal of the Belarusian State University. Sociology, 2019)
The situation in Soviet genetics in prewar and postwar years is described. The data on historical prerequisites, organization, and holding of this session are given. The consequences of session decision for development of Soviet genetics is discussed.
Keywords: genetics; genes; agrobiology; agriculture; session for position in genetics 1948; All-Union Lenin Academy of Agriculture Sciences